Studi Kinerja Biaya dan Waktu (Studi Kasus: Proyek Pembangunan Gedung F Poliklinik Terpadu RSUD Prof. Dr. Soekandar) - Priambudi, Alfian Wahyu; Qordhowi , Andrian Firdaus Yusuf Al (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
In good project management, we don't just look at quality and quality aspects, we also have to consider the reality on the ground from cost and time aspects. Costs that do not exceed budget and completion time faster than planned means that the project is an indication of having a good team and project management. One of the methods applied here is the value acquisition method to determine performance from cost and time aspects. Its function is to determine the value of cost deviations and time deviations during implementation until the end of the project so that it can determine steps and decisions to speed up project completion. The application of the value acquisition method is carried out by analyzing 5 interconnected indicators, namely ACWP, BCWP, BCWS, CV, SV, CPI and SPI. The analysis results obtained up to week 25 are as follows. BCWS = Rp. 29,573,910,264; BCWP = Rp. 27,168,467,824; ACWP = Rp. 24,451,620,962 then obtained SV value = - 2,405,442,440; CV = Rp. 2,716,846,862; SPI = 0.919; CPI = 1.111;. From the results of the calculation of the five interrelated variables, it can be concluded that the Integrated Polyclinic Building F construction project has good cost performance and is economical, while the time performance is poor and the schedule is behind schedule.